International court jurisdiction in disputes concerning unlawful use of trademarks on the internet - Tomáš Gongol; Radka Zahradníková (DANUBE: Law, Economics and Social Issues Review, 2019)
The rapid development of IT technologies in the last fewdecades has also created increasing number of cross-border disputes. This trend is affected by the fact, that there are no border lines thatwe can find in the realworld. Different lawsystems have to deal with the existence of this new, on state borders independent entity. In the perspective of law, internet is interesting because of its inability as a virtual space, to fit in the doctrine of legal state, by which the state exercises its authority and enforces its law on its territory. This traditional bond between the state, its territory and its law system is impaired, sometimes it is referred to as virtualization or delocalization of legal relationships. Delocalization has a great influence on determination of the decisive law system and court jurisdictions. In those cases, we need to distinguish substantive law and procedural law in order to determine court (or other institution) jurisdiction and law system which would be applied on the case. With regard to the topic of this article, we will deal with private law relationships with international elements. Unlawful use of trademarks on the internet raises a number of issues. One example is the use of trademarks on the internet and to what extent such use is infringing trademark rights on a specific territory. This paper deals particularly with the jurisdictional issues and how rules on private international law can assist in resolving these issues. The currently applicable EU Brussels I Regulation (Recast) allows infringers to be sued either in the place of the defendant's domicile or in the place of the harmful event.
Keywords: 330; Court Jurisdiction; European Union; Internet; Trademarks